2018
DOI: 10.1101/246710
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-linear transfer characteristics of stimulation and recording hardware account for spurious low-frequency artifacts during amplitude modulated transcranial alternating current stimulation (AM-tACS)

Abstract: 21Background: Amplitude modulated transcranial alternating current stimulation (AM-tACS) has 22 been recently proposed as a possible solution to overcome the pronounced stimulation artifact 23 encountered when recording brain activity during tACS. In theory, AM-tACS does not entail 24 power at its modulating frequency, thus avoiding the problem of spectral overlap between brain 25 signal of interest and stimulation artifact. However, the current study demonstrates how weak 26 non-linear transfer characteristic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…1a). Although the recording was continued during stimulation, signals acquired during this period were discarded from the analysis due to the massive electromagnetic stimulation artifact, that can currently not be reliably removed from resting state recordings [51][52][53][54] .…”
Section: Magnetoencephalogrammentioning
confidence: 99%
“…1a). Although the recording was continued during stimulation, signals acquired during this period were discarded from the analysis due to the massive electromagnetic stimulation artifact, that can currently not be reliably removed from resting state recordings [51][52][53][54] .…”
Section: Magnetoencephalogrammentioning
confidence: 99%
“…presence of higher frequency components, total charge) influence neurophysiological response (Song et al 2015;Patel & Butera, 2018); or if isolators distortion is not-linear (e.g. low frequency content is introduced) the experiment may be fundamentally compromised (Franke et al 2014;Kasten et al 2018). In the case of amplifiers and electrodes, the cost of band-width limits will reflect the experimental design.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Amplifier and electrode attenuation may not be critical for conventional neurophysiological measures (e.g. action potential threshold or rate, low frequency oscillation power; Grossman et al 2017;Negahbani et al 2018) unless (1) stimulation artifact removal depends on accurate field pick-up (Helfrich et al 2014;Dowsett and Herrmann 2016); (2) when recording hardware non-linearities are of concern (Lesperance et al 2018; Kasten et al 2018); (3) when electrophysiological responses at kHz rate (e.g. kHz fluctuations in membrane potential) are of interest (Pelot et al 2017); and (4) when interactions between equipment and the body introduce complex distortions (Neuling et al 2017;Noury and Siegel, 2018;Gebodh et al 2019).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…In principle, this would effectively avoid any spectral overlap between the brain signals of interest (here near 10 Hz) and the artefact of tACS (here 220 Hz ± 10 Hz). However, preliminary work suggests the M/EEG spectrum remains corrupted near the modulation frequency (Minami and Amano, 2017;Kasten et al, 2018b), though to a much lesser extent than observed during monosinusoidal tACS.…”
Section: Limitations and Future Directionsmentioning
confidence: 90%
“…There is growing evidence that AM-tACS can entrain oscillations at the frequency of the envelope Witkowski et al, 2016;Minami and Amano, 2017), though may require greater stimulation intensities (Negahbani et al, 2018) than mono-sinusoidal tACS. Unfortunately, some artefact still remains at the modulation frequency, likely arising from additional nonlinearities at the level of the stimulator or recording hardware (Kasten et al, 2018b) or from the analog/digital conversion (Minami and Amano, 2017). Without these hardware nonlinearities, AM-tACS would well tolerate heartbeat-and respiration-related modulations (Figure 5.3), with the physiologically derived symmetry also occurring around the 220 Hz carrier-clever use of the type of AM-tACS can minimise this symmetry, even delivered with the same envelope frequency (see Appendix D).…”
Section: Dealing With Tacs Artefactsmentioning
confidence: 99%